Side effects of psychotropic drugs on eye - A.A. Petukhova; A.A. Panov; Ya.V. Malygin; M.A. Kazanfarova (РМЖ "Клиническая офтальмология", 2021)
A.A. Petukhova1, A.A. Panov1, Ya.V. Malygin2, M.A. Kazanfarova3 1Lomonosov Moscow State University, Moscow, Russian Federation 2A.I. Evdokimov Moscow University of Medicine and Dentistry, Moscow, Russian Federation 3Skolkovo Innovation Center, Moscow Region, Russian Federation Any antipsychotics provoke more or less ocular complications. Some of them are relatively harmless (i.e., dark eyelids, conjunctival and corneal pigmentation, mydriasis, nystagmus, dry eye etc.). These adverse effects are resolved spontaneously after treatment discontinuation, drug switching, or prescribing additional therapy. However, the intake of both typical and atypical neuroleptics, lithium salts, some anticonvulsants (e.g., topiramate) is associated with high risks of vision loss. Moreover, in some patients these medications may result in blindness. The use of psychotropic drugs (e.g., tricyclic antidepressants or serotonin reuptake inhibitors) in patients with higher risk of acute angle closure is of particular concern. The association between phenothiazines and anticonvulsants and retinopathy, chlorpromazine and cataract, anticonvulsants and poor color vision and reduced contrast sensitivity is also important. Psychiatrists and ophthalmologists should consider potenti al ocular side effects in patients receiving psychotropic drugs. Knowing management algorithm for these conditions is also important. The number of recent publications on this issue is limited. Therefore, articles older than 10 years are sometimes used. Keywords: eye, visual organ, adverse effects, psychotropic drugs, neuroleptics, tricyclic antidepressants, selective serotonin reuptake inhibitors, glaucoma, retinopathy, cataract. For citation: Petukhova A.A., Panov A.A., Malygin Ya.V., Kazanfarova M.A. Side effects of psychotropic drugs on eye. Russian Journal of Clinical Ophthalmology. 2021;21(1):29–33. DOI: 10.32364/2311-7729-2021-21-1-29-33.